Tanggung Jawab Pelaku Usaha Perusahaan Penyedia Jasa Dalam Pasar Digital Perdagangan Mata Uang - Andreas Kurnia; Christine S.T. Kansil (IAIN Langsa, 2025)
Ideally, the digital currency trading market operates within a framework of strong business responsibility, transparency, and consumer protection. However, in reality, digital currency trading practices are still characterized by high risks to users, limited service transparency, and unclear boundaries of liability for service provider companies. This condition raises fundamental legal issues regarding the position and obligations of business actors within the rapidly evolving digital market ecosystem. This study aims to analyze the concept and forms of responsibility borne by service provider companies in the digital currency trading market, as well as to identify the challenges in its practical implementation. The research employs a library-based study with a qualitative approach, utilizing normative legal analysis supported by statutory and conceptual approaches. Data sources consist of relevant regulations, legal literature, and scholarly journal articles. The findings indicate that business actors bear legal responsibilities encompassing system security, information transparency, consumer protection, and transaction risk management. Strengthening regulatory frameworks, ensuring effective supervision, and fostering ethical commitments among business actors are essential to establishing a fair, secure, and sustainable digital currency trading market.